Reform of The Islamic Education System in Indonesia According to Azyumardi Azra - Marhamah; Abdul Hakim Abdullah (Islam Universalia: International Journal of Islamic Studies and Social Sciences, 2020)
Rapid technological change requires Islamic educational institutions to make changes in various aspects, fundamentally and comprehensively so that Islamic education is able to face the global challenges of education towards civil society. If not, he will be left far behind from modern education. In Indonesia, Azyumardi Azra is one of the professors who is concerned in the field of education whose thoughts can be used as role models in the reform of Indonesian Islamic education. The study of the concept of renewal of the Islamic education system according to Azyumardi Azra was reviewed based on the social background and historical setting of the renewal of Islamic education that took place in the early XX century in Indonesia. Azyumardi's thoughts Azra helped to give a new color to Islamic educational institutions in Indonesia, besides introducing new systems and methods, educational figures at that time also integrated general sciences into the curriculum of Islamic education so that it could bring Islamic schools and higher education. This study is descriptive analysis using a sociological historical and social hermeneutical approach. The method of study in the form of content analysis namely analysis of the text content and hermeuneutic analysis based on the interpretation of his books and his papers. Azyumardi Azra sees the reformation of the Islamic education system is very important that functions as an instrument in the creation of Indonesian human resources that have intellectual, spiritual, and moral. The results of this study can be concluded that the acceptance of a modern Islamic education system is projected to play a more constructive role in welcoming civilized societies capable of integrating Islamic, scientific, and Indonesian-oriented educational systems. The Islamic element is a great concern for the classical Islamic treasures which enables the emergence of educational results that have spiritual qualities. The scientific element compromises general science with religious knowledge. While the Indonesian element is intended because the pesantren institution is used as a reference for future education. the concept of cohesiveness in the education system is used as a philosophical reference framework for education that is capable of producing leaders and at the same time has an Islamic scientific ethos in civic education. This is clearly seen in the grounding of universal Islamic values at the time of the reform of the Islamic higher education system initiated by Azyumardi Azra. Abstrak Perubahan dan kemajuan teknologi yang pesat menuntut lembaga pendidikan Islam melakukan perubahan dalam berbagai aspek, secara mendasar dan menyeluruh agar pendidikan Islam mampu menghadapi tantangan global pendidikan menuju masyarakat madani. Jika tidak, ia akan tertinggal jauh dari pendidikan modern. Di Indonesia, Azyumardi Azra adalah salah seorang guru besar yang konsen dalam bidang pendidikan yang pemikirannya dapat dijadikan sebagai rol model dalam pembaharuan pendidikan Islam Indonesia. Kajian tentang konsep pembaharuan system pendidikan Islam menurut Azyumardi Azra dikaji berdasarkan latar belakang sosial dan setting sejarah pembaharuan pendidikan Islam yang terjadi pada awal abad XX di Indonesia. Pemikiran Azyumardi Azra ikut memberikan warna baru bagi lembaga pendidikan Islam di Indonesia, disamping memperkenalkan sistem dan metode baru, tokoh-tokoh pendidikan ketika itu juga memadukan ilmu-ilmu umum kedalam kurikulum pendidikan Islam sehingga melahirkan madrasah dan pendidikan tinggi Islam. Kajian ini bersifat descriptive analisis dengan menggunakan pendekatan historis sosiologis dan hermeunetik social. Metode kajiannya berupa: Contens analisis yakni analisis isi dari teks dan hermeuneutik analisis yakni interpretasi buku-buku dan tulisan-tulisannya. Azyumardi Azra melihat eksistensi pembaharuan sistem pendidikan Islam sangat penting yang berfungsi sebagai instrumen dalam penciptaan SDM Indonesia yang memiliki intelektual, spiritual, dan moral. Hasil kajian ini dapat disimpulkan bahwa penerimaan sistem pendidikan Islam yang modern diproyeksikan dapat berperan lebih konstruktif menyongsong masyarakat berperadaban yang mampu mengintegrasikan sistem pendidikan berwawasan keislaman, keilmuan, dan keindonesiaan. Unsur keislaman merupakan perhatian besar terhadap khazanah Islam klasik yang memungkinkan lahirnya hasil pendidikan yang memiliki kualitas spiritual. Unsur keilmuan mengkompromikan ilmu umum dengan ilmu agama. Sedangkan unsur keindonesiaan dimaksudkan karena institusi pesantren yang dijadikan rujukan pendidikan masa depan. konsep keterpaduan dalam sistem pendidikan tersebut dijadikan kerangka rujukan filosofis pendidikan yang mampu melahirkan pemimpin dan sekaligus memiliki etos keilmuan Islam dalam pendidikan kewarganegaraan (civil education). Ini terlihat jelas dalam pembumian nilai-nilai Islam universal pada saat pembaharuan sistem pendidikan tinggi Islam yang digagas oleh Azyumardi Azra DOI: https://doi.org/10.5281/zenodo.4033005